Garment Reuse in Practice: Insights from a Clothing Swap - Vermeyen, Veerle; Germeys, Filip (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Reuse is a key strategy to intensify the use of goods. Hence, clothing swaps are typically presented as a sustainable alternative to conventional fashion consumption. However, research into the mechanisms and dynamics behind these exchanges remains limited. Using qualitative and quantitative methods to study a swapping event in a city in Belgium, this study explores the potential of clothing swaps to enable the reactivation and reuse of clothing. The mass flow analysis reveals that about half of the garments brought to an in-person swap using an indirect exchange system found new owners. Certain garment types (t-shirts and sweaters) were more easily swapped than others (pants). Survey responses indicated that participants use swaps to hand off dormant clothing that is no longer suited to their needs. Further, participant stated that most of the garments they acquired will substitute the purchase of garments. When comparing the wardrobe composition of swap participants to a general sample, we found that swappers have a similar wardrobe size but a much higher fraction of pre-owned garments. Unexpectedly, swap participants had a slightly higher fraction of dormant garments in their wardrobes. The observed differences cannot be solely attributed to participation in swap events, as participants are likely also engaged in other reuse activities. Meaning it provides an important glimpse into the potential effects society-wide policies focused on increasing garment reuse could have on wardrobes. To summarize, by combining different methods, this study provides new insight into the dynamics behind swapping, and clothing reuse in general.